Rethinking National Literatures and the Literary Canon in Scandinavia - Lönngren, Ann-Sofie, 1974-; Grönstrand, Heidi; Heede, Dag; Heith, Anne, 1955- (Cambridge Scholars Publishing, 2015)
The literary field and canon in the Nordic countries are under constant negotiation and transformation, with various alternative literatures having evolved alongside the majority literatures of these nations in recent decades. These new phenomena, constructed around perspectives regarding language, ethnicity, sexuality, gender and social class, have been categorised as migration, minority and queer literatures. Rethinking National Literatures and the Literary Canon in Scandinavia highlights these literatures and their histories, roles and impacts on both the literary establishment and (post)mo.